Modifying an Active Compound S Release Kinetic Using a Supercritical Impregnation Process to Incorporate an Active Agent into Pla Electrospun Mats - Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Lopez de Dicastillo-Bergamo, A; Villegas-Vallejos, C; Roa-Ruiz, K; Garrido-Ayala, L (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The main objective of this work was to study the release of cinnamaldehyde (CIN) from electrospun poly lactic acid (e-PLA) mats obtained through two techniques: (i) direct incorporation of active compound during the electrospinning process (e-PLA-CIN); and (ii) supercritical carbon dioxide (scCO2) impregnation of CIN within electrospun PLA mats (e-PLA/CINimp). The development and characterization of both of these active electrospun mats were investigated with the main purpose of modifying the release kinetic of this active compound. Morphological, structural, and thermal properties of these materials were also studied, and control mats e-PLA and e-PLACO2 were developed in order to understand the effect of electrospinning and scCO2 impregnation, respectively, on PLA properties. Both strategies of incorporation of this active compound into PLA matrix resulted in different morphologies that influenced chemical and physical properties of these composites and in different release kinetics of CIN. The electrospinning and scCO2 impregnation processes and the presence of CIN altered PLA thermal and structural properties when compared to an extruded PLA material. The incorporation of CIN through scCO2 impregnation resulted in higher release rate and lower diffusion coefficients when compared to active electrospun mats with CIN incorporated during the electrospinning process. © 2018 by the authors.